Effects of Diode Laser 940 nm with and without 5 % Sodium Fluoride White Varnish with Tri-calcium Phosphate on Dentin Permeability (In vitro study) - Al-khafaji, Zahraa R.; Awazli, Lutfi G.; Al-Maliky, Mohammed A. (Iraqi Journal of Laser, 2017)
It is found that hypersensitive teeth have a larger number and wider patent tubules than those of non-sensitive teeth. Objective: The aim of this study is to compare between the effects of diode laser at different power densities, with and without sodium fluoride on the sealing of exposed dentinal tubules and dentin permeability. Materials and methods: 118 teeth were used. Samples were divided into three major groups. The first consisted of 100 teeth used for permeability test. The second consisted of 16 teeth for measuring external surface temperature elevation while irradiation. The third, in turn, consisted of one pair of teeth observed under SEM for dentine surface morphology analysis. Results: For dentin permeability measurement, the results revealed a highly significant difference between the control group and 2, 3 W with varnish groups. For the external surface temperature elevation, the results revealed that temperature rise, for both laser alone and with varnish groups, was between (67-97.9 ∘C) at 1.6, 2 W. SEM analysis revealed that approximately optimum sealing of tubules occurred in 2W with the varnish group. Conclusions: The combined application of 940 nm diode laser at 2W with 809.7 W/cm² power densities, with sodium fluoride white varnish show a significant improvement in their effects on dentin permeability reduction as compared to each treatment alone.